Diversified exercise programmes in physical education for female students - Poddubnaya, T.V.; Ryabchuk, V.V.; Lyashenko, O.V.; Panov, S.N. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a methodology for using multidirectional exercise complexes in physical education for female students. Methods and structure of the study. The following methods were used: pedagogical experiment, assessment of physical fitness level, functional tests, questionnaires, surveys, bioimpedance analysis of body composition and measurement of body parameters, methods of mathematical statistics. Thirty-four multidirectional complexes of functional physical exercises were compiled with a description of the methods of their application. Results and conclusions. The methodology contains: physical exercises of functional training and recommendations for their use in training sessions and in the training process; an individual approach to each student, taking into account her level of physical fitness and training goals; the use of modern technologies for distance learning and self-monitoring.